(untitled) (International Journal of Environmental Sciences, 2025)
Background: Hospital Management Information Systems (HMIS) are critical for improving healthcare delivery, yet their effective utilization depends on healthcare professionals’ knowledge, attitudes, and practices (KAP). Objective: To assess KAP regarding HMIS among healthcare professionals in a tertiary care teaching hospital in Jharkhand, India. Methods: A descriptive cross-sectional study was conducted among 400 healthcare professionals using a pre-tested questionnaire. Data analysis was performed with SPSS v22, applying descriptive statistics, Pearson correlation, and t-tests. Results: Of the respondents, 88.2% were aware of HMIS, but only 31.7% had formal training. Medium levels were recorded for knowledge (77.5%), attitude (86.5%), and practice (83.2%). Knowledge correlated positively with attitude (r = 0.145, p = 0.004). No significant differences in KAP were observed based on gender or age. Conclusion: Findings highlight the need for targeted HMIS training, improved usability, and supportive institutional policies to enhance system adoption.